Analysing the potential vulnerabilities in online voting protocols: homomorphic encryption approach - Azameti, Charles Yao; Asiedu, William; Asante, George (UiTM Cawangan Perlis, 2025)
Online voting offers a hopeful alternative to traditional voting approaches by improving accessibility, efficiency, and transparency in elections. However, despite their potential, these systems are prone to a variety of security vulnerabilities. This research aims to analyze the crucial vulnerabilities that can compromise the integrity, confidentiality, and availability of online voting systems. Key threats examined include cyber-attacks such as denial of service (DoS), man-in-the-middle (MITM) attacks, and malware injection, as well as issues related to voter authentication, anonymity, and coercion resistance. Additionally, the research evaluates the effectiveness of cryptographic techniques like homomorphic encryption, zero-knowledge proofs, and blockchain in mitigating these risks. The study provides a comprehensive review of existing protocols, identifies gaps in their security architectures, and proposes enhanced mechanisms to address the vulnerabilities. The ultimate goal is to contribute to the development of more robust and secure online voting systems that ensure voter trust and uphold democratic principles.